Exposure to COVID-19 Vaccine Hesitancy Is as Impactful as Vaccine Misinformation in Inducing a Decline in Vaccination Intentions in New Zealand: Results from Pre-Post Between-Groups Randomized Block Experiment - Thaker, Jagadish; Subramanian, Arun (Frontiers in Communication, 2021)
While recent studies have investigated how health messages on vaccine characteristics shift public intentions to get a COVID-19 vaccine, few studies investigate the impact of real-world, widely shared vaccine misinformation on COVID-19 vaccine acceptance. Moreover, there is currently no research that investigates how exposure to hesitancy, as compared to misinformation, is associated with COVID-19 vaccination intentions. Based on data from a nationally representative survey experiment conducted in March 2021 (N=1083), exposure to outright COVID-19 vaccine misinformation as well as exposure to vaccine hesitancy induces a decline in COVID-19 vaccination intentions to protect self and to get the vaccine to protect others in New Zealand, compared to factual information from government authorities. Moreover, there is no significant difference in exposure to misinformation or hesitancy in self-reported change in COVID-19 vaccination intentions. However, respondents are more likely to believe in vaccine hesitancy information and share such information with family and followers compared to misinformation. Implications for research in health communication campaigns on COVID-19 are presented.